Microactuators and Micromechanisms Proceedings of MAMM-2016, Ilmenau, Germany, October 5-7, 2016 - Zentner, Lena.; Corves, Burkhard; Jensen, Brian; Lovasz, Erwin-Christian.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book brings together investigations which combine theoretical and experimental results related to such systems as capsule micromechanisms, active micro catheters, nanotube vascular stents, mechanisms for micromilling, different compliant mechanisms including grippers and compliant systems with actuators and sensors, microrobots based on vibrations, tactile sensors, tooth brackets, compliant valves, and space reflectors. This volume contains twenty-two contributions from researchers from ten countries, represented at the 4th Conference on Microactuators and Micromechanisms, which was held in 2016 in Ilmenau, Germany. The aim of the conference was to provide a special opportunity for a know-how exchange and collaboration in various disciplines concerning systems pertaining to micro-technology. This Conference was organized under the patronage of IFToMM (International Federation for the Promotion of Mechanism and Machine Science). .
Keywords: EXTC Engineering; Control, Robotics, Mechatronics; Biomedical Engineering/Biotechnology.; Nanotechnology and Microengineering